Effects of Cryogenic Treatment on the Friction and Wear Properties andMicrostructure of TC4 Titanium Alloy - ZHANG Liang, YU Xiao-jian (Cailiao Baohu)
At present, the mechanism of the influence of cryogenic treatment on the mechanical properties and microstructure of TC4 titanium alloy has not been analyzed clearly. Herein, the effects of cryogenic treatment with different cryogenic times on the wear properties, surface microhardness and microstructure of TC4 titanium alloy were investigated by hardness test, friction and wear performance test, scanning electron microscope (SEM) and transmission electron microscope (TEM). Results showed that the wear resistance and surface microhardness of TC4 titanium alloy were improved to different extents after the cryogenic treatment with different times. Meanwhile, cryogenic treatments could induce lot of dislocation structures inside the materials, which played an important role in improving the microhardness and wear resistance of the treated materials.